MHC-II distance between parents predicts sex allocation decisions in a genetically monogamous bird. (9th November 2021) - Pineaux, Maxime; Merkling, Thomas; Danchin, Etienne; Hatch, Scott A; Leclaire, Sarah; Blanchard, Pierrick
Abstract: Theory predicts that parental heritable characteristics should shape sex allocation decisions when their effects on reproduction or survival are offspring sex-dependent. Numerous studies have questioned to what extent characteristics displayed by one of the parents matched theoretical expectations. This contrasts with the handful of studies that investigated whether compatibility between parents could also trigger selective pressures for sex allocation adjustments. We studied the genetically monogamous black-legged kittiwake ( Rissa tridactyla ), where previous data revealed that female chicks suffered higher fitness costs from low diversity at genes of the major histocompatibility complex (MHC) than male chicks. We predicted, and found in our dataset, that MHC-similar parents, producing low MHC-diverse offspring, should avoid the production of females. The relation between MHC-distance between parents (i.e. the functional distinctness of their MHC alleles) and offspring sex was not linear, such that MHC-dissimilar parents also overproduced sons. Overall, our results suggest that the genetically monogamous black-legged kittiwake parents flexibly adapt their reproduction and circumvent the costs of suboptimal pairing by manipulating offspring sex. Abstract : When parental characteristics affect offspring reproduction or survival in a sex-dependent way, parents should choose to have the sex that performs best. In the black-legged kittiwake, a lack of diversity at immune genes has strong negative effects in daughters, but not in sons. Accordingly, we show that when kittiwake parents are at risk of producing low genetically diverse offspring, they avoid producing daughters. Our results further suggest that it may be advantageous for parents to produce high genetically diverse sons.